Effect of Lactic Acid Bacteria on the Pharmacokinetics and Metabolism of Ginsenosides in Mice - Ji-Hyeon Jeon; Jaehyeok Lee; Jin-Hyang Park; Chul-Haeng Lee; Min-Koo Choi; Im-Sook Song (MDPI AG, 2021)
This study aims to investigate the effect of lactic acid bacteria (LAB) on in vitro and in vivo metabolism and the pharmacokinetics of ginsenosides in mice. When the in vitro fermentation test of RGE with LAB was carried out, protopanaxadiol (PPD) and protopanaxadiol (PPD), which are final metabolites of ginsenosides but not contained in RGE, were greatly increased. Compound K (CK), ginsenoside Rh1 (GRh1), and GRg3 also increased by about 30%. Other ginsenosides with a sugar number of more than 2 showed a gradual decrease by fermentation with LAB for 7 days, suggesting the involvement of LAB in the deglycosylation of ginsenosides. Incubation of single ginsenoside with LAB produced GRg3, CK, and PPD with the highest formation rate and GRd, GRh2, and GF with the lower rate among PPD-type ginsenosides. Among PPT-type ginsenosides, GRh1 and PPT had the highest formation rate. The amoxicillin pretreatment (20 mg/kg/day, twice a day for 3 days) resulted in a significant decrease in the fecal recovery of CK, PPD, and PPT through the blockade of deglycosylation of ginsenosides after single oral administrations of RGE (2 g/kg) in mice. The plasma concentrations of CK, PPD, and PPT were not detectable without change in GRb1, GRb2, and GRc in this group. LAB supplementation (1 billion CFU/2 g/kg/day for 1 week) after the amoxicillin treatment in mice restored the ginsenoside metabolism and the plasma concentrations of ginsenosides to the control level. In conclusion, the alterations in the gut microbiota environment could change the ginsenoside metabolism and plasma concentrations of ginsenosides. Therefore, the supplementation of LAB with oral administrations of RGE would help increase plasma concentrations of deglycosylated ginsenosides such as CK, PPD, and PPT.